Idiom Translation Strategies in English Version of Hirata’s Edensor - Sari Dwi Rahayu; Sri Minda Murni (LINGUISTIK TERAPAN, 2016)
This research dealt with the idiom translation strategies. The objectives of this study were: (1) to describe the types of idiom translation strategies in Edensor novel; (2) to describe the context of idiom translation strategies are applied in Edensor novel. The data were obtained from the idiom translation strategies in Edensor novel both its original and English version. This research applied qualitative research design. The data were collected through documentation and observation by reading the novel and listing the idioms found. The findings of this study have revealed that: 1). There were four types of idiom translation strategies in Edensor novel found, they are using an idiom of similar meaning and form (6.9%), using an idiom of similar meaning but dissimilar form (3%), translating an idiom by paraphrase(79,2%) and translating idiom by word for word (10,9%).While, the omission strategy was not found in this study; 2) the context applied in translating Indonesian idioms in Edensor novel into its English version were linguistic context and social cultural context. Keywords: translation strategies, context of idiom